The effect of exercise training proposed private means to develop Passing and its relationship to focus attention of the young players in football - Nagi, Deyaa (Journal of Physical Education, 2015)
The research aims to propose a way of training for the development of precise handling and exercises of their own and then see their relationship to focus attention when football players were placed exercises skill private media of the proposed assumed researcher that means the proposed contribute to achieving the goals of research and that the exercise of the proposed development of precise handling as well as there is a relationship to focus attention carefully handling and researcher chose young players representing the Police Club football aged (17-19 years) and the number of research sample (20) player divided the sample into two experimental (10) players and officer (10) players have been applied experience for (8) weeks and instead (3) training units per week and during which the use of the means proposed training and exercises to develop the precision handling of the experimental group either control group are to develop skills such as handling means training available to them and with the team coach and under the supervision of the researcher and the researcher concluded that the method proposed training with exercise has achieved the goals of the research and recommended its use for the development of skills and especially the handling of the age groups in football